Analysis of foreign tourists' satisfaction with the quality of accommodation offer in the city of Belgrade - Milena Podovac; Slobodan Ivanović; Vedran Milojica (UTMS Journal of Economics, 2022)
The subject of Research in this paper is the satisfaction of foreign tourists with the quality of the accommodation offer in the city of Belgrade, which represents the most developed and most visited tourist destination in the Republic of Serbia. The research was conducted on a sample of 262 foreign respondents, who stayed and used accommodation services in Belgrade. The results of the research showed that foreign tourists are mostly satisfied with the quality of the accommodation offer, and it was concluded based on the average scores that the degree of satisfaction is highest in the case of the location of the accommodation facilities and the competence and friendliness of the employees. However, the degree of satisfaction of foreign tourists with the quality of the accommodation offer in Belgrade is not at an enviable level when it comes to the availability of additional facilities in the accommodation facility and the organization of various types of events. Based on the results of the research, the authors defined guidelines for improving the quality of the existing accommodation offer in the city of Belgrade, as well as recommendations for future research
Keywords: L83; Z32; Z39; 330; satisfaction; foreign tourists; accommodation offer; Belgrade